Circularly polarized antennas - Gao, Steven; Luo, Qi, 1982-; Zhu, Fuguo (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2014)
This book addresses a broad range of topics on circularly polarized antennas including design techniques for different types of CP antennas (small-size CP antennas, broadband CP antennas, multi-band CP antennas and CP arrays) and antenna technologies (microstrip antennas, helix, quadrifilar helix antenna, printed quadrifilar helix antenna, dielectric resonator antennas, printed slots, spiral antennas, monopoles, waveguide slot arrays, reflectarrays, active arrays, millimetre-wave arrays in LTCC, electronically beam-switching arrays and electronically beam-steerable arrays). It includes numerous case studies demonstrating how to design and implement different CP antennas in practical scenarios. This book is of value for researchers; system engineers (antenna, telecom, space and satellite); postgraduates studying the subjects of antenna and propagation, electromagnetics, RF/microwave/millimetre-wave systems, satellite communications and so on; technical managers and professionals in the areas of antennas and propagation. --
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Spiral antennas; Transmitting antennas; Antenna radiation patterns; Polarized beams (Nuclear physics); TECHNOLOGY & ENGINEERING -- Mechanical; Antenna radiation patterns; Polarized beams (Nuclear physics); Spiral antennas; Transmitting antennas; Electronic books